1988
DOI: 10.2337/diab.37.1.21
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Streptozocin-Induced Diabetes in Mice: Electron Microscopy Reveals Single-Cell Insulitis Before Diabetes Onset

Abstract: We investigated the morphology of mouse islets 5 days after completion of low-dose streptozocin treatment of C57BL/6 mice by electron microscopy. At this stage, mice were still normoglycemic and light microscopy did not reveal massive islet infiltration. The electron-microscopic investigation revealed two characteristics indicative of ongoing islet cell destruction. In all islets investigated, lysed islet beta-cells were recognized by disrupted plasma membranes and concomitantly decreased plasma contrast. Many… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
0
2

Year Published

1992
1992
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(66 citation statements)
references
References 12 publications
3
61
0
2
Order By: Relevance
“…The results of our current study confirm the findings of others who have reported that LDS-induced insulitis is characterized by both lymphocytic and histiocytic infiltrates and that the latter precedes the former [16][17][18]. Our study also confirms our previous observation that EFA deficiency decreased the severity of lymphocytic insulitis in LDS-treated mice [10,11,12].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The results of our current study confirm the findings of others who have reported that LDS-induced insulitis is characterized by both lymphocytic and histiocytic infiltrates and that the latter precedes the former [16][17][18]. Our study also confirms our previous observation that EFA deficiency decreased the severity of lymphocytic insulitis in LDS-treated mice [10,11,12].…”
Section: Discussionsupporting
confidence: 83%
“…Herald et al [16] and Kantwerk et al [17] demonstrated with immunohistochemistry large numbers of CD4-positive and CD8-positive cells. Later, Kolb-Bachofen et al [18] demonstrated that, prior to onset of insulitis and diabetes, macrophages infiltrated the islets and they termed this "single cell insulitis". The same group also demonstrated that single cell insulitis played an important role in the onset of LDS diabetes by demonstrating that treatment with silica, a macrophage toxin, was more protective than T-cell depletion [19].…”
Section: Discussionmentioning
confidence: 99%
“…Beta-cell destruction following multiple low-dose STZ treatment has been shown to involve islet infiltration by both macrophages and lymphocytes, 31,32 thus recapitulating, in part, the known etiology of type-1 diabetes. As shown in Figure 3c, mice receiving either DsAAV-MIP-eGFP or vehicle alone had AAV-mediated expression of GLP-1 in beta-cells MJ Riedel et al significantly higher blood glucose levels than those receiving DsAAV8-MIP-GLP-1 as measured by twoway, repeated-measures analysis of variance.…”
Section: Dsaav8-mip-glp-1 Protects Against Stz-induced Diabetes In Vivomentioning
confidence: 99%
“…Macrophages have been repeatedly shown to play a crucial role in early phases of disease development in animal models: they constitute the major infiltrating cell type during early insulitis in BB rats [1], NOD mice [2] and low-dose streptozotocintreated mice [3]. Impairment of maerophage function prevents disease manifestation in these animals [3][4][5]. Activated but not resident macrophages were found to rapidly and effectively kill islet ceils but not hepatocytes or thyroeytes [6].…”
Section: Introductionmentioning
confidence: 99%